Evaluasi Tarif Kereta Api Perintis Dengan Metode ATP-WTP (Studi Kasus: KA Jenggala) - Imron, Nanda Ahda; Aghastya, Adya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
Mojokerto and Sidoarjo are two strategic and connected region in East Java which generate a significant travel demand. KA Jenggala (“perintis” subsidies) is one of public transport choice connected those area that has served for 5 years with rates Rp.4.000,00 per trip. The cheapness of subsidies ticket is good for pssengers but on the other hand it creates significant burden to state budget. This study aims to obtain a balance point from both sides. Using the ATP WTP method, it found that ATP value is Rp.11.552,00 and existing WTP is Rp.4.000,00. When passenger offered with the service improvement that are cash and cashless ticketing systems, frequency increase, journey and waiting time reduction and on-time performance improvement, the WTP value becomes Rp.6.500,00. The price adjustment by Rp.6.500,00 is welcomed by passenger if the service improvement implemented.